Answer:
-1
Explanation:
Move all terms containing x
to the left side of the equation.
Tap for fewer steps...
Subtract 4x from both sides of the equation.
2 x−10−4x= −8 y=4x−8
Subtract 4 x from 2 x − 2 x− 10= − 8 y = 4 x − 8
Move all terms not containing x to the right side of the equation.
Tap for more steps...
− 2 x = 2 y = 4 x − 8
Divide each term by − 2 and simplify.
Tap for fewer steps...
Divide each term in − 2 x= 2 by − 2 .
− 2 x − 2 = 2 − 2 y = 4 x − 8
Simplify the left side of the equation by cancelling the common factors.
Tap for fewer steps...
Reduce the expression by cancelling the common factors.
Tap for more steps...
− ( − 1 ⋅ x ) = 2 2 y = 4 x − 8
Rewrite
− 1 ⋅ x as - x . x = 2 − 2 y = 4 x − 8
Divide 2 by − 2 .
x = − 1 y = 4 x − 8
Replace all occurrences of x with the solution found by solving the last equation for x . In this case, the value substituted is − 1 . x= − 1 y = 4 ( − 1 ) − 8
Simplify 4 ( − 1 ) − 8 .
Tap for fewer steps...
Multiply 4 by − 1 .
x = − 1 y = − 4 − 8
Subtract 8 from - 4 .
x = − 1 y = − 12
The solution to the system of equations can be represented as a point.
( − 1 , − 12 )
The result can be shown in multiple forms.
Point Form: ( − 1 , − 12 )
Equation Form: x =− 1 ,y = − 12